Is the percentage of hormone receptor positivity in HR+ HER2-metastatic breast cancer patients receiving CDK 4/6 inhibitor with endocrine therapy predictive and prognostic? - Keskinkilic, Merve; Semiz, Huseyin Salih; Yavuzsen, Tugba; Oztop, Ilhan (Frontiers in Oncology, 2024)
Purpose: There is no clear information in the literature about the relationship between the efficacy of CDK 4/6i combined with ET and HR positivity. However, we know that the longest overall survival was in the ER-strong positive/PR intermediate or strong positive groups. Therefore, we aimed to investigate CDK4/6i treatments that create positivity in HR. Methods: Patients with the diagnosis of HR+/HER2-MBC who were treated with CDK 4/6i and HR >10% were retrospectively evaluated. To analyze the role of HR positivity, ER was moderately positive (10-49%) and ER was strongly positive (50-100%); PR was grouped as moderately positive (10-49%) and PR strongly positive (50-100%).Results: Median follow-up of 150 patients included in the study was 15.2 months (95% CI, 2.1-40.9 months). The highest response in the whole group was obtained in the ER-strong positive/PR moderate or strong positive group, and the ER moderate positive/PR moderate or strong group. This was followed by the ER strong positive/PR negative group, and then the ER moderate positive/PR negative group. Although these advantages were not statistically significant, they were numerically higher (ORR: 83.8% vs. 83.3% vs. 77.4% vs. 62.5%, p=0.488, respectively). The highest survival in the whole group was achieved in the ER strong positive/PR moderate or strongly positive group, followed by the ER moderately positive/ PR moderate or strongly positive group, the ER strongly positive/PR negative group followed by the ER moderate positive/PR negative group, respectively(p=0.410). However, these advantages were not statistically significant. Conclusion: As a result, HR+/HER2-MBC patients receiving CDK 4/6i combined with ET suggest that the percentage of HR positivity may have a predictive and prognostic role.